1962
DOI: 10.1126/science.138.3536.34
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Stratification in Lake Fryxell, Victoria Land, Antarctica

Abstract: A landlocked lake of sodium-mixed-anion type in lower Taylor Valley has a salinity ranging from 1/35 to 1/5 that of sea water. The lake seems to be chemically stratified into three distinct layers. Several possible sources are postulated for the dissolved salts. The chemical zonation may have been initiated by past climatic variation; however, a thermal or magmatic origin for some of the waters is also indicated. No single origin for the lake waters or the stratification seems likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…This is supported by the fact that this valley is located in the Ross Island volcanic area (ARMITAGE and HouSE, 1962;ANGINO et al, 1962ANGINO et al, , 1965. (b) High salt concentrations resulted from evaporation of sea water after the lake was isolated from the ocean (ANGINO and ARMITAGE, 1963;CRAIG 1966;NICHOLS, 1963).…”
Section: Methodsmentioning
confidence: 85%
“…This is supported by the fact that this valley is located in the Ross Island volcanic area (ARMITAGE and HouSE, 1962;ANGINO et al, 1962ANGINO et al, , 1965. (b) High salt concentrations resulted from evaporation of sea water after the lake was isolated from the ocean (ANGINO and ARMITAGE, 1963;CRAIG 1966;NICHOLS, 1963).…”
Section: Methodsmentioning
confidence: 85%
“…Gooseff et al (2002) found that Cl ) and Na + also shared these sources, but that dissolved K + came primarily from chemical weathering. Angino et al (1962) suggest that thenardite (Na 2 SO 4 ) dissolution contributes Na + to stream water chemistry, and Claridge and Campbell (1977) attributed dissolved K + concentrations to dissolution of muscovite micas.…”
Section: Study Sitementioning
confidence: 99%
“…Clearly, the chemical evolution of the surface water in the valley relates initially to the variation in glaciochemistry (Lyons et al, 1998). Although the closed-basin lakes that receive the meltwaters have very different geochemistries (Angino et al, 1962;Lyons and Mayewski, 1993;Lyons et al, 1998), previous investigations have given little thought to the idea that variations in glacier chemistry could be partially responsible for the chemical differences in the lakes. Taylor Valley has been studied extensively since the International Geophysical Year , however, virtually no information is available on the chemistry of precipitation or the glaciochemistry in the region.…”
Section: Introductionmentioning
confidence: 97%